STUDIES ON ORGANOGENESIS FROM NODAL EXPLANT OF RUTA GRAVEOLENS L. - D. H. TEJAVATHI; B. L. MANJULA (The Bioscan, 2010)
Ruta graveolens L., commonly known as Rue is widely exploited for its active principles which are of high pharmaceutical value. In vitro techniques were employed to multiply and conserve this traditional medicinal plant. Nodal explants were cultured on Murashige and Skoog’s medium supplemented with various growth regulators. Direct and indirect regeneration from the cultures were observed depending on the media composition. MS + 2, 4-D (2.26μM) + Kin(9.29μM) + GA3 (1.44μM) was found to be best for direct regeneration, while MS+NAA(10.74μM)+BAP(13.20μM)+L-glutamine (1.36mM) + GA3 (2.88μM) for indirect regeneration from the callus raised on NAA supplemented medium. Rooting of the regenerated shoots was obtained on ½ MS + NAA (0.01μM) + L-glutamine (1.36mM). Acclimatized plants are maintained in Botanical garden of the department. About 95% survivals were recorded.